Penerapan Aplikasi Pencatatan Keuangan Digital Bagi Ibu Rumah Tangga di Perumahan Mekarsari, Kota Depok: Literasi Keuangan Menggunakan Aplikasi Money Manager dan Excel Sederhana - Jayanto, Imam; Lubis, Aminah; Hamzah , Ramadhani; Ningtyas, Harfiahani Indah Rakhma; Durya, Ngurah Pandji Mertha Agung (Prisani Cendekia, 2024)
The ability to manage household finances effectively is a crucial aspect in maintaining the stability and resilience of the family economy, especially amidst the dynamics of daily needs that continue to grow. However, the reality in the field shows that most housewives still face limitations in terms of financial literacy, especially in recording income and expenses systematically and structured. Based on these problems, this community service activity aims to improve the financial literacy of housewives in Mekarsari Housing, Depok City, through training in the use of digital financial recording applications. The methods used include face-to-face training sessions, direct application usage practice, and intensive assistance during the implementation process. The two main applications introduced in this training are Money Manager for mobile-based recording and Microsoft Excel as a simple but flexible recording tool. Evaluation was carried out through pre-tests and post-tests as well as observations of participant practice. The results showed a significant increase in understanding the basic concepts of financial literacy, technical skills in using the application, and awareness of the importance of daily financial recording. This program not only has a positive impact on the technical skills of participants but also encourages the creation of a culture of financial discipline and economic independence in the household environment. In the future, this training is expected to be replicated in other community environments as a strategic effort to empower the family economy based on digital technology.